STRATEGY TO REDUCE COAL HAULING CYCLE TIME TO INCREASE THE PRODUCTIVITY IN PT ADARO INDONESIA - Jil Helga; Yuanita Handayati; Adirizal Nizar (Universitas Islam Lamongan, 2023)
PT Adaro Indonesia (AI) is one of the largest thermal coal producers in Indonesia with production of around 40-50 million tons per year. AI’s mine business processes are managing mining production operations and selling to customers. To transport coal from production sites to sales points, AI travels by land and river. This paper will focus on transportation by land. Land coal transportation is carried out from the Stockpile/ROM (run-of-mine) to the Barito River Port in Kelanis Dedicated Coal Terminal using a coal trailer with capacity of 140-ton through dedicated hauling road along 86 km. one coal hauling cycle takes approximately five hours. It includes loading time in the stockpile, hauling time, weighing time on the weighing bridge and dumping time at Kelanis, then back to the Stockpile. In the period of January – April 2022, the average hauling cycle time is 5 hours 14 minutes which means exceeding the agreed time at the beginning of the year which was 5 hours. This has an impact on the non-achievement of sales target in the period that ultimately has an impact on not achieving the company’s revenue target. The focus on this research is to analyze the root cause of the non-achievement of cycle time targets on the dedicated hauling road and will identify the solutions to improve the conditions. The methods used are quantitative and qualitative to obtain data and information from various company stakeholders. The root cause of the problem is identified based on the data then validated based on the results of interviews and literature studies. The problems concluded from this study are transportation time and weighing time. The hauling time is affected by the average travel speed of the trailer, while the weighing time is affected by the change shift of trailer operator. Therefore, we recommended solution to increase the average travel speed of the trailers based on the root cause analysis is to increase road maintenance, while to reduce weighing time is to reschedule the number trailer operator shifts.